PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR - Latief, Hilman (Jurnal Pendidikan Geografi Gea, 2014)
Learning is an activity that can result in changes in a person, both actual and potential. Learning will be more meaningful if the child has learned what not to know. One of the methods that position the active role of students in this study is a method of contextual learning. Issues raised in this study is whether there are differences in initial test scores and final scores as well as differences in learning outcomes in the experimental class using contextual learning and classroom control using conventional methods. The design used in this study is a quasi experimental, Nonequivalent (Pretest and posttest) Control-Group Design on class VII SMP 4 Padalarang. The independent variables are contextual learning. The dependent variable is the student learning outcomes. Testing the difference of the average pretest and posttest score results using the t test at significance level α = 0.05, with a basis for decision making Ho is accepted if t t table, otherwise the Ho is rejected if t count t table. The result of the calculation is the average difference using t-test at α = 0.05, df 39 is obtained t = 6.773, whereas the t table = 11.099. Because it uses a two-sided test, the acceptance region is a table-t ≤ t ≤ t table. Meanwhile t (6.773) t table (1.690), therefore the Ho = accepted. From the calculation of N-gain per class research 12.5% of students were high, 72.5% medium category and 15% lower category. From these calculations it can be concluded occur influence learning outcomes were greater in the experimental class than the control class. The conclusion of this study that there is a significant effect of contextual learning on learning outcomes as indicated by he change in the value of better learning outcomes than the value of the results of the previous study on class VII SMP 4 Padalarang Keywords: Contextual Teaching and Learning, Learning Outcomes, Pretest, Posttest, N-Gain